Sustainability Awareness Profile of Locational School Students Through ESD-Oriented Project Based Learning - Nur Khoiri; M. Syaipul Hayat; Dyah Siskawati (Postgraduate, University of Mataram, 2023)
Education in Indonesia seeks to realize sustainable development through the implementation of ESD in Vocational High Schools (SMK). Even though ESD has been attempted in Indonesia, especially in the world of vocational school level education, based on the results of observations in the field, it turns out that learning in the classroom is still not fully directed towards Sustainable Development Education, even though it can actually be integrated well, for example in the science and technology project learning. ESD is very important in building students' mindset and lifestyle in the present and future, so this research was carried out to obtain more concrete information regarding students' sustainability awareness profiles through the integration of ESD in the science project learning, which is deemed to be beneficial. supporting students' sustainability awareness. The researcher carried out a quantitative research approach using the Oneshot case study method through a survey with a random sample of 482 students in 2 vocational schools in Semarang Regency online using a Descriptive Analytical method. The instrument used was a questionnaire with a Likert scale (without neutral options) which was given after the learning process. Through this research, data was obtained that Sustainability Awareness (Sustainability Awareness) in the emotional and behavioral and attitude categories includes the